From Anglo-Saxon Roots to Modern English: A Linguistic Journey (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article begins by setting the stage for an exploration of the evolution of the English language from its Anglo-Saxon roots, emphasizing the dynamic nature of language as a reflection of culture and history. It provides a detailed account of the origins of Old English, its regional variations, and its grammatical complexities. The article examines the influences of Celtic culture, Christianity, and cultural blending on Old English vocabulary and grammar. A noteworthy section explores the literature of the Anglo-Saxon period, shedding light on literacy and the pivotal role of King Alfred. The article discusses the lasting impact of Old English on Modern English, highlighting the continuity and survival of Old English words. The conclusion underscores the importance of understanding the Anglo-Saxon language to fully grasp the evolution of Modern English. The article is well-researched and provides a comprehensive overview of the topic. However, it could benefit from more contemporary examples to illustrate the continuity of Old English in today’s language.